2005
DOI: 10.1152/ajprenal.00122.2005
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafishslc4a2/ae2anion exchanger: cDNA cloning, mapping, functional characterization, and localization

Abstract: Although the zebrafish has been used increasingly for the study of pronephric kidney development, studies of renal ion transporters and channels of the zebrafish remain few. We report the cDNA cloning and characterization of the AE2 anion exchanger ortholog from zebrafish kidney, slc4a2/ae2. The ae2 gene in linkage group 2 encodes a polypeptide of 1,228 aa exhibiting 64% aa identity with mouse AE2a. The exonintron boundaries of the zebrafish ae2 gene are nearly identical to those of the rodent and human genes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 65 publications
1
40
1
Order By: Relevance
“…Of at least 14 different transporters capable of Na + -independent anion exchange in the gene families SLC4 (Alper 2006;Romero et al, 2004) and SLC26 (Mount and Romero, 2004), many have been identified in fish (Shmukler et al, 2005;Musch and Goldstein, 2005;Guizouarn et al, 2005;Renfro and Pritchard, 1983;Pelis and Renfro, 2003;Piermarini et al, 2002). The SLC26 gene family contains at least two (of >10) candidate genes likely to be involved in intestinal anion exchange: A3 and A6 (also known as DRA, downregulated in ademona and PAT1, putative anion transporter 1), which, in mammals, are abundant in the apical membrane of the intestinal mucosa (Mount and Romero, 2004).…”
Section: Nature Of the Anion Exchange Protein(s)mentioning
confidence: 99%
See 1 more Smart Citation
“…Of at least 14 different transporters capable of Na + -independent anion exchange in the gene families SLC4 (Alper 2006;Romero et al, 2004) and SLC26 (Mount and Romero, 2004), many have been identified in fish (Shmukler et al, 2005;Musch and Goldstein, 2005;Guizouarn et al, 2005;Renfro and Pritchard, 1983;Pelis and Renfro, 2003;Piermarini et al, 2002). The SLC26 gene family contains at least two (of >10) candidate genes likely to be involved in intestinal anion exchange: A3 and A6 (also known as DRA, downregulated in ademona and PAT1, putative anion transporter 1), which, in mammals, are abundant in the apical membrane of the intestinal mucosa (Mount and Romero, 2004).…”
Section: Nature Of the Anion Exchange Protein(s)mentioning
confidence: 99%
“…Likely alternative genes from the SLC26 family include SLC26a2 and SLC26a4 (pendrin) and a possible candidate from the SLC4 family is SLC4a3 of which all are expressed apically in mammalian HCO 3 -secreting epithelia (Alper, 2006;Mount and Romero, 2004). In addition, SLC4a2, which is preferentially expressed in the basolateral region of the mammalian kidney, was recently shown to have largely apical localization in the zebrafish pronephric duct epithelium and to be stimulated by hypertonicity (Shmukler et al, 2005). Due to the apical localization of teleost SLC4a2 and the stimulation by hypertonicity, this SLC4 transporter can also be considered a likely candidate contributing to intestinal anion exchange in the marine teleost intestine.…”
Section: Nature Of the Anion Exchange Protein(s)mentioning
confidence: 99%
“…Similarly, SLC26A1 has been implicated in renal sulfate transport in eel (Anguilla japonica) (Nakada et al, 2005) and rainbow trout . Little is known about the role of SLC4 Cl -/HCO 3 -exchangers in the fish kidney although SLC4A2 (AE2) has been identified in the kidney of larval zebrafish (Shmukler et al, 2005;Shmukler et al, 2008 . Second, one or more of the anion transporters may be operating in an electrogenic mode.…”
Section: A Comparison Of the Fish Gill And Mammalian Kidneymentioning
confidence: 99%
“…Expression of jagged and notch genes in the pronephros suggests that they could play an important role in patterning the pronephric nephron (Zecchin et al, 2005). Evidence for nephron patterning in the pronephros is seen in the segment-specific expression of ion transporters Shmukler et al, 2005), in the expression of receptors and transcription factors in discrete segments (Bisgrove et al, 1997;Marcos-Gutierrez et al, 1997;Van Campenhout et al, 2006), and in the disruption of segment-boundary formation in the pax2.1 (also known as pax2a -Zebrafish Information Network) mutant no isthmus (Majumdar et al, 2000). In our examination of cilia function in the kidney (Kramer-Zucker et al, 2005) we have found that two types of ciliated cells exist in the pronephros: single ciliated cells that have the morphology of typical transporting epithelial cells, and multiciliated cells that, by several criteria, appear specialized for fluid propulsion in the pronephros.…”
Section: Introductionmentioning
confidence: 99%